Analisis Hukum Tata Negara Terhadap Otonomi Daerah Dalam Pengelolaan Sumber Daya Alam - Ronald Thomas Mendrofa; Tri Setiadi; Lia Pratiwi (University of Muhammadiyah Malang, 2026)
This study examines issues of regional autonomy in natural resource management (NRM) within Indonesia from a constitutional law perspective. The primary problems stem from overlapping authorities between central and regional governments alongside regulatory disharmony that impedes sustainable development and equitable distribution of NRM benefits. This research aims to analyze the constitutional legal framework governing regional autonomy in NRM, map out regulatory inconsistencies, and propose legal solutions comprising a harmonization model based on constitutional interpretation and mechanisms for resolving authority disputes. The study employs a normative juridical method utilizing statutory and conceptual approaches. Key findings indicate a pressing need for regulatory alignment, strengthening of local institutional capacity, and effective dispute resolution mechanisms. The novelty of this research lies in offering a harmonization model grounded in the principle of authority proportionality and a comparative analysis with other developing countries (the Philippines and India) facing similar challenges. The results are expected to provide policy recommendations for lawmakers and the executive branch in achieving equitable and sustainable NRM through enhanced regional autonomy.